Answer:
y = -2x - 4
Step-by-step explanation:
We transform the line equation of L:
2x + y = 3 --(-2x)--> f(x) = y = -2x + 3
We now know that L intersects the y-axis at 3 and it has a slope of -2.
In order to construct a parallel line M, it needs to have an identical slope to L.
All we need to do now is to move one step from the given point (1,-6) towards 0 with the predetermined slope of -2, resulting in the point (0,-4).
Since we know slope and intersection with the y-axis (0,-4), we can construct the line equation:
f(x) = y = -2x - 4 for line M.